Morphometric diversity of wild poisonous arbila (Phaseolus lunatus) germplasm from Timor and Sumba Islands, Indonesia - AGNES V. SIMAMORA; LINCE MUKKUN; MAYAVIRA V. HAHULY; PETRONELLA SAHYANTI NENOTEK; YOSEP SERAN MAU; NORMAN RIWU KAHO; YOSEPH NAHAK SERAN; ENOS TANGKE ARUNG; EVERT Y. HOSANG (Society for Indonesian Biodiversity, 2026)
Abstract. Simamora AV, Mukkun L, Hahuly MV, Nenotek PS, Mau YS, Kaho NR, Seran YN, Arung ET, Hosang EY. 2026. Morphometric diversity of wild poisonous arbila (Phaseolus lunatus) germplasm from Timor and Sumba Islands, Indonesia. Biodiversitas 27 (5): d270511. https://doi.org/10.13057/biodiv/d270511. Poisonous arbila (Phaseolus lunatus) is an underutilized legume traditionally consumed after detoxification by dryland communities in East Nusa Tenggara, Indonesia. Despite its importance as an emergency food resource, information on its phenotypic variation remains limited. This study aimed to characterize seed morphometric variation in wild and semi-managed arbila germplasm collected from six locations across Timor and Sumba Islands. A total of 108 accessions were evaluated using twelve seed traits, including eight qualitative characters (seed shape, seed coat color and pattern, hilum shape, testa texture, and eye color) and four quantitative characters (seed length, width, thickness, and 100-seed weight). Qualitative traits showed high polymorphism, particularly in seed coat pigmentation and patterning, while quantitative traits exhibited wide ranges (seed length: 10.33-23.70 mm; 100-seed weight: 25.40-56.50 g). Multivariate analyses (principal component analysis and hierarchical clustering) indicated that the first four principal components explained 91.6% of the total variance, with seed size–related traits dominating the primary axis (PC1 = 65.2%). Clustering results identified one major group comprising most accessions and a small number of divergent accessions, consistent with a continuous phenotypic gradient rather than discrete group separation. These results highlight considerable morphometric diversity in arbila and indicate that phenotypic differentiation is primarily structured along this gradient. The findings provide a useful basis for germplasm conservation and highlight the potential of arbila for selection, breeding, and future studies on domestication and genetic diversity.